MENSTRUATION AND POWER POLITICS IN CONTEMPORARY SOCIETY: A REVIEW OF LITERATURE - M. K., Anjaly Nair; G. M., Tungesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Menstruation, apart from being considered a normal menstruation process, is also a socially constructed phenomenon shaped by cultural norms, power dynamics, and language. The stigma and shame surrounding menstruation are silencing women by reinforcing the notion of inferiority and impurity, which are ways to perpetuate power imbalances in society. Menstruating women are restricted from participating in religious and sacred ceremonies and this cultural practice of considering menstruating women as the ‘other’ in the society plays a key role in constructing power politics in the society. The present paper deals with analysing various studies on menstruation to find out the views of various writers on menstruation. The present study aims to analyse how societal attitudes and practices related to menstruation can mirror and perpetuate power imbalances. This study also attempts to find out how menstruation plays a key role in constructing power politics in contemporary society.